Role of cajuput waste compost against the physical quality of sandy soil - M Mashudi; Zaenal Kusuma; S Soemarno; Sugeng Prijono (Journal of Degraded and Mining Lands Management, 2019)
Composting is an alternative way to accelerate decomposition and maturation of residual waste from refining leaves of cajuput to be suitably applied to the soil. The application of Cajuput Waste Compost (CW Compost) is intended to increase the productivity of sandy soil in Indonesian dryland. Compost serves as a soil conditioner that can improve the physical, chemical and biological properties. The study aimed to determine and analyze the role of CW compost in improving the physical quality of sandy soil in two incubation periods. The study used experimental methods, through soil incubation that given CW compost, in a greenhouse with two incubation periods. The experiments used a completely randomized design with 4 levels of CW compost treatment, namely: 0 t/ha (P0), 10 t/ha (P1), 20 t/ha (P2), 30 t/ha (P3). The results showed CW compost had a significant role in improving the physical quality of sandy soil both at 1-month and 4-month incubations. The soil physical quality increased by increasing compost levels and incubation periods, except for the total available water variable which decreased after 4-month incubation. The decrease was allegedly due to the reduction of labile fraction in the soil